2017
DOI: 10.3847/2041-8213/aa93fc
|View full text |Cite
|
Sign up to set email alerts
|

On the Progenitor of Binary Neutron Star Merger GW170817

Abstract: On 2017 August 17 the merger of two compact objects with masses consistent with two neutron stars was discovered through gravitational-wave (GW170817), gamma-ray (GRB170817A), and optical (SSS17a/AT 2017gfo) observations. The optical source was associated with the early-type galaxy NGC 4993 at a distance of just ∼40 Mpc, consistent with the gravitational-wave measurement, and the merger was localized to be at a projected distance of ∼2 kpc away from the galaxy's center. We use this minimal set of facts and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 94 publications
1
48
0
1
Order By: Relevance
“…While for binary neutron stars, the beamed electromagnetic emission can constrain the orbital plane and thus improve the distance and the Hubble constant measurements [76,77], for BWD the H 0 measurement precision benefits from a higher rate of joint detections due to the isotropic emission of SN type Ia with respect to the GRB and a brighter emission with respect to a kilonova, and from a higher astrophysical rate of BWD with respect to the BNS rate (the white-dwarf merger rate is about 1-2 orders of magnitude higher than for BNS) [78,79]. Indeed, the projected constraints discussed so far can be further improved by stacking multiple GW observations.…”
Section: Discussionmentioning
confidence: 99%
“…While for binary neutron stars, the beamed electromagnetic emission can constrain the orbital plane and thus improve the distance and the Hubble constant measurements [76,77], for BWD the H 0 measurement precision benefits from a higher rate of joint detections due to the isotropic emission of SN type Ia with respect to the GRB and a brighter emission with respect to a kilonova, and from a higher astrophysical rate of BWD with respect to the BNS rate (the white-dwarf merger rate is about 1-2 orders of magnitude higher than for BNS) [78,79]. Indeed, the projected constraints discussed so far can be further improved by stacking multiple GW observations.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the GCMF, the observations rule out a cluster at the position of GW170817 at a level of ∼ 4σ below the mean. (Abbott et al 2017c;Blanchard et al 2017). Overall, these studies found consistency between the progenitor properties and the distributions of Galactic binary neutron stars which formed via isolated binary evolution (e.g., Wong et al 2010).…”
Section: Constraints On a Globular Cluster Originmentioning
confidence: 99%
“…Mapelli & Giacobbo (2018) used binary population synthesis coupled together with cosmological simulation to study dependence of double NSs merger rate on natal kicks. They found that it was necessary to assume extremely small value of σ = 15 km s −1 for the Maxwellian velocity distribution to reproduce the double NSs merger rate derived from the gravitational wave detection GW170817 (Abbott et al 2017). There is a group of Be X-ray binaries with small eccentricities and large orbital periods (Pfahl et al 2002;Townsend et al 2011) which require natal kicks of v < 50 km s −1 to explain their observational properties.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the natal kick distribution for neutron stars (NSs) is important because it is an essential ingredient of models for double NSs formation, in particular the double NS mergers (Abbott et al 2017), short gamma-ray bursts, millisecond pulsars formation and different scenarios for white dwarfs-NS mergers (Toonen et al 2018). Natal kicks are essential to model the Galactic distribution of pulsars and eventually design radio surveys to discover new NSs.…”
Section: Introductionmentioning
confidence: 99%